Ocena innowacyjności Polski na podstawie rankingu innowacyjności 2005 - Kozioł, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents the results of the European Innovation Scoreboard - an instrument of the European Commission for the annual follow-up of the Lisbon strategy. The report includes data from the EU countries, the Associate countries and the Candidate countries. The aim of the paper is to compare the data between Poland and the EU member countries. Based on SII score, the European countries can be divided into four groups: - Switzerland, Finland, Sweden, Denmark, and Germany make up the group of "Leading countries", - France, Luxembourg, Ireland, United Kingdom, Netherlands, Belgium, Austria, Norway, Italy, and Iceland all belong to the group of countries showing "Average performance", - Countries "Catching up" are Slovenia, Hungary, Portugal, the Czech Republic, - Lithuania, Latvia, Greece, Cyprus, and Malta, - Countries "Losing ground" are Estonia, Spain, Bulgaria, Poland, Slovakia, - Romania, and Turkey. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 191-199